Comparable worth of life for all?: conducting and disseminating health economic evaluations for refugees in Germany - Biddle, Louise; Wahedi, Katharina; Bozorgmehr, Kayvan (Globalization and health, 2022)
Comparative health economic evaluation is based on premise of being able to compare the worth of a year of life lived in full quality across different patients, population groups, settings and interventions. Given the rising numbers of forcibly displaced people, the nexus of economics, migration and health has emerged as a central theme in recent conceptual and empirical approaches. However, some of the assumptions made in conventional economic approaches do not hold true in the decision-making context of migration and the health of forcibly displaced populations. Using the experience of conducting and disseminating economic analyses to support decision-making on health screening policies for refugees in Germany, we show that in particular the assumptions of individual utility with no positive externalities, equity-blind utilitarian ethical stances and stable budgets are challenged. The further development of methods to address these challenges are required to support decision-makers in this contentious and politically fraught context and continue to make choices and decisions transparent.